Bronhoblokation's complications in the treatment of pneumoempyema - V. Komarchuk (Kazimierz Wielki University, 2017)
It was described features of use the bronchial valves in patients with pneumoempyema,techniques of procedure. We described the complications as sociated with using of bronchial valves, and methods of their elimination.